2014
DOI: 10.1111/mec.13003
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal ability and habitat requirements determine landscape‐level genetic patterns in desert aquatic insects

Abstract: Species occupying the same geographic range can exhibit remarkably different population structures across the landscape, ranging from highly diversified to panmictic. Given limitations on collecting population-level data for large numbers of species, ecologists seek to identify proximate organismal traits-such as dispersal ability, habitat preference and life history-that are strong predictors of realized population structure. We examined how dispersal ability and habitat structure affect the regional balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 59 publications
5
101
1
Order By: Relevance
“…It plays a decisive role in species diversity and ecosystem diversity. It is also the basis of population survival, development and evolution (Barrett and Kidwell 1998;Phillipsen et al 2015). The polymorphic loci percentage of S. grandis and S. krylovii populations (90.20 and 93.54 % respectively) and the total Nei's genetic diversity indices (He) (0.2522 and 0.2261 respectively) detected in this research are similar to that previously reported for these two species.…”
Section: Population Of Stipa Species Show Rich Genetic Diversitysupporting
confidence: 87%
See 1 more Smart Citation
“…It plays a decisive role in species diversity and ecosystem diversity. It is also the basis of population survival, development and evolution (Barrett and Kidwell 1998;Phillipsen et al 2015). The polymorphic loci percentage of S. grandis and S. krylovii populations (90.20 and 93.54 % respectively) and the total Nei's genetic diversity indices (He) (0.2522 and 0.2261 respectively) detected in this research are similar to that previously reported for these two species.…”
Section: Population Of Stipa Species Show Rich Genetic Diversitysupporting
confidence: 87%
“…A common approach used in landscape genetic studies is to compare the matrices between genetic distances and geographic or landscape distance of isolated populations in large scales . However, recent studies have increasingly conducted on the individuals or populations that continuously distributed across small spatial scales to understand micro-evolutionary processes (Anderson et al 2010;Cushman and Landguth 2010;Freedman et al 2010;Zancolli et al 2014;Phillipsen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Following recent research in landscape genetics (e.g. Phillipsen et al., ; Van Strien, Keller & Holderegger, ), we used minimum likelihood population effect (MLPE, Clarke, Rothery & Raybould, ) to account for the non‐independence of the distance matrices. In this method, the random effect of the model incorporates a parameter (p) that accounts for the proportion of the total variance due to the correlation between distances that originates from the same sampling sites.…”
Section: Methodsmentioning
confidence: 99%
“…; Phillipsen et al . ), but they also indicate that it is complicated to obtain accurate predictions about the degree of habitat fragmentation beyond of which population genetic structure and diversity are affected due to complex interactions among multiple influential factors (Lange et al . ; Callens et al .…”
Section: Conclusion and Implications For Conservationmentioning
confidence: 99%